(untitled) (Research, Society and Development, 2021)
The use of 3D printers in medical practice has increased, being an innovation that positively helps the teaching-learning process involving visual and kinesthetic learning. The present study describes the use of reverse engineering in the production of 3D models and its applicability in the medical teaching-learning context. This is an integrative literature review carried out from searches in the PubMed, LILACS, SciELO and Academic Google databases, using the descriptors “Medical Education”, “Tridimensional Printing” and “Computer-Aided Design”. Reverse engineering makes it possible to obtain CAD (computer aided design) models of objects from image exam data, resulting in a highly detailed technical drawing, and in highly realistic 3D printer printed parts. 3D parts can be used in the study of human anatomy, in clinical and surgical cases. The applicability of these models is already observed around the world and in Brazil. The parts allow a better understanding of complex anatomical points, diseases, and their relationship with the treatment, in addition to anatomical variations. In the context of medical teaching-learning, reverse engineering can be inserted in practical classes, so that the student can manipulate the image exams and reproduce the pieces in 3D and digital resources, increasingly inserted in the globalized world. Therefore, there is a great growth opportunity for the medical school that makes use of 3D parts, having as great allies the low cost and high anatomical precision of reverse engineering printing.